1999
DOI: 10.1046/j.1471-4159.1999.0730867.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Equilibrative, Nitrobenzylthioinosine‐Sensitive Nucleoside Transporters (ENT1) in Brain

Abstract: Nucleoside transport processes may play a role in regulating endogenous levels of the inhibitory neuromodulator adenosine in brain. The cDNAs encoding species homologues of one member of the equilibrative nucleoside transporter (ENT) gene family have recently been isolated from rat (rENT1) and human (hENT1) tissues. The current study used RT-PCR, northern blot, in situ hybridization, and [ 3 H]nitrobenzylthioinosine autoradiography to determine the distribution of mRNA and protein for ENT1 in rat and human bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 36 publications
2
56
1
2
Order By: Relevance
“…Therefore, ENT1 equilibrative nucleoside transporter could be involved in this effect, which is in line with the observation that the effect of ATP was temperature dependent. This finding corroborates with the distribution of this transporter in the central nervous system, including the hippocampus, and its role in the transmembrane carriage of extracellular nucleosides (Glass et al, 1996;Anderson et al, 1999). The observation that adenosine was more efficient than uridine in eliciting [ H]purine efflux in the hippocampus.…”
Section: B Sperlágh Et Alsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, ENT1 equilibrative nucleoside transporter could be involved in this effect, which is in line with the observation that the effect of ATP was temperature dependent. This finding corroborates with the distribution of this transporter in the central nervous system, including the hippocampus, and its role in the transmembrane carriage of extracellular nucleosides (Glass et al, 1996;Anderson et al, 1999). The observation that adenosine was more efficient than uridine in eliciting [ H]purine efflux in the hippocampus.…”
Section: B Sperlágh Et Alsupporting
confidence: 83%
“…Yet another possibility is that ATP is secreted by CD39 protein, recently recognized as an ATP-transporting protein (Bodas et al, 2000). As the ENT1 nucleoside transporters are distributed on nerve terminals and also on astrocytes and endothelial cells (Anderson et al, 1999), the cellular source of ATP-evoked purine efflux could be either nerve terminals, glial cells or endothelial cells. Since no similar ATP-or ADP-induced purine accumulation was observed in isolated hippocampal nerve terminals (Cunha, 2001b), it seems likely that nonneuronal elements expressing the ENT1 transporter provide a major contribution to this effect.…”
Section: B Sperlágh Et Almentioning
confidence: 99%
“…Cellular release and uptake of adenosine in the brain are mediated by several types of membranous nucleoside transporters (Hyde et al, 2001;Lee et al, 2001;Baldwin et al, 2004). Recent work has shown that NTrans are expressed and functional in rodent hippocampus (Anderson et al, 1999;Sperlagh et al, 2003). Indeed, challenging NTrans with inosine (Yao et al, 1997;Li et al, 2001) reversed the outward current induced by BzATP (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…First, microarray data from FACSpurified neurons show that both developing (P7 and P16) and adult (older than P20) neurons express ENT1 and ENT2 (43,44). Second, in situ hybridization studies in rat brain tissue demonstrate that cortical tissue and the hippocampal CA1 region express ENT1 (45,46). We used this information to manipulate adenosine release from CA1 neurons by administering inosine intracellularly as a competitive substrate to adenosine.…”
Section: Discussionmentioning
confidence: 99%